STRUCTURE AND DEVELOPMENT OF VIRUSES AS OBSERVED IN THE ELECTRON MICROSCOPE : V. WESTERN EQUINE ENCEPHALOMYELITIS VIRUS - Morgan, Councilman (The Rockefeller University Press, 1961)
Stages in the development and release of Western equine encephalomyelitis virus are illustrated and described. It is suggested that precursor particles 22 mµ in diameter differentiate at template sites close to membranes bordering cytoplasmic vacuoles and that these particles either pass into the lumen of the vacuole, acquiring in the process a coat and peripheral membrane, or are dispersed in the cytoplasm and extruded through the cellular wall, emerging as viral particles on the surface. Although necrosis and dissolution of the cell with release of contents, including virus, may intervene at any stage of infection, ejection of virus from the vacuoles presumably can occur without rupture of the cell. The virus consists of a 30 mµ core separated by a zone of lesser density from a sharply defined peripheral membrane 45 to 48 mµ in diameter. Precursor particles, as well as viral particles, occasionally crystallize, the former in the cytoplasm, the latter in vacuoles and probably on the cellular surface.